2017
DOI: 10.1002/qua.25561
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical prediction for complex organic molecules

Abstract: Numerous types of quantum chemical calculations and protocols have been successfully applied to computing pK a of small, uncomplicated organic molecules. Here, we argue for the need to shift attention to more challenging molecules that are marked by an interplay of complicating factors such as conformational, tautomeric, steric, and other effects. The challenge is not in choosing the right quantum chemical method and solvation model but in combining the existing methods to simultaneously and accurately describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 29 publications
(42 reference statements)
0
43
0
1
Order By: Relevance
“…42 After using Epik, uncertainty remained for ligands 13 and 21 which was resolved with Schrödinger's macro-pKa prediction protocol. 43 As 2HOG is missing residues 44 to 50 as well as the side chain for TYR 20, PDB entry 2E9V (resolved at 1.9 Å, 0.65 Å backbone RMSD from 2HOG) was used as the starting protein structure for FEP. The oxygen positions of the unperturbed three-water network were also taken from 2E9V.…”
Section: Chk1mentioning
confidence: 99%
See 1 more Smart Citation
“…42 After using Epik, uncertainty remained for ligands 13 and 21 which was resolved with Schrödinger's macro-pKa prediction protocol. 43 As 2HOG is missing residues 44 to 50 as well as the side chain for TYR 20, PDB entry 2E9V (resolved at 1.9 Å, 0.65 Å backbone RMSD from 2HOG) was used as the starting protein structure for FEP. The oxygen positions of the unperturbed three-water network were also taken from 2E9V.…”
Section: Chk1mentioning
confidence: 99%
“…Schrödinger's method to determine macro-pKas was run on the remaining ligands to estimate the pKas of the aromatic nitrogens. 43 These predictions, shown in Table 4, have an expected error of about 1 pKa unit, making the protonation state of ligands 2d, 6d, and 8d in solvent uncertain. A correction, described previously, 51 was applied to predicted relative free energies to account for the pKa of the ligands in solvent.…”
Section: Urokinasementioning
confidence: 99%
“…Table 2 shows the 7-fold CV and external validation statistics for optimal models. These were derived using PLS (4…”
Section: Resultsmentioning
confidence: 99%
“…Recently 2 , Connolly suggested that a lack of experimental information on both relative tautomer stability and the properties of distinct tautomeric forms are the likely causes of such issues. Tautomeric species present a challenge, not just to empirical-based approaches, but also to those that attempt to solve the pK a prediction problem using first-principles [1][2][3][4][5] . For tools implementing the latter approach (e.g.…”
mentioning
confidence: 99%
“…However, if they are close, the macroscopic pKa is shifted as multiple microscopic transitions contribute to the macroscopic value. Several studies [40, 41] discuss this in greater detail. In our method, we calculate microscopic pKa value for each acid-base pair of microscopic states.…”
Section: Theorymentioning
confidence: 99%